UMPSA Maulidur Rasul celebration marked with vibrancy and colour - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 9 October 2024 - The Maulidur Rasul celebration at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) was marked with a colourful parade themed 'Al-Falah Pemacu Malaysia MADANI'.